Prevalence, Influencing Factors, and Clinical Characteristics of Cognitive Impairment in Elderly Patients With Schizophrenia - Liu, Guojun; Zhang, Xiaoying; Huo, Xiaoning; Li, Wei (Frontiers in Psychiatry, 2022)
Abstract Aims: The purpose of this study was to investigate the prevalence, influencing factors and cognitive characteristics of cognitive impairment in elderly patients with chronic schizophrenia. Methods: A total of 264 elderly patients with chronic schizophrenia and 156 normal controls were enrolled in the current study. The Mini-mental State Examination (MMSE) was used to assess their overall cognitive function, the Positive And Negative Syndrome Scale (PANSS) was used to assess their psychotic symptoms, the Geriatric Depression Scale (GDS) was used to assess their depressive symptoms, while Activity of Daily Living Scale (ADL) was used to assess their daily living ability. Results: The prevalence of cognitive impairment was 77.7% (205/264) in elderly patients with chronic schizophrenia, which was much higher than that in normal controls 16.7 % (26/156). By using stepwise binary regression analysis, we found that hobbies (p<0.001, OR=0.224, 95%CI:0.114-0.441) might be a protective factor for cognitive impairment, and this relationship remained statistically significant after adjusting for total scores of GDS, ADL and PANSS (modelb)(p=0.016, OR=0.406, 95%CI:0.195-0.847). Compared with individuals without cognitive impairment, individuals with cognitive impairment tend to have more depression and psychiatric symptoms as well as worse activities of daily living (p<0.05). Through linear regression analysis of the mediating model, we found that hobbies may improve cognitive function by improving psychiatric symptoms, and play a partial mediating role (B=-4.789, p<0.001). Conclusions: Cognitive impairment is a very prominent problem in elderly patients with chronic schizophrenia. Elderly schizophrenia patients with cognitive impairment tended to have more depressive mood, more psychotic symptoms and worse activities of daily living. However, hobbies will help prevent cognitive impairment in elderly patients with schizophrenia and may improve their cognitive function by influencing psychiatric symptoms. Therefore, we should encourage elderly patients with chronic schizophrenia to develop their own hobbies. Keywords: elderly, chronic schizophrenia, cognitive impairment, hobby, MMSE.